Exploring the complexities of temporomandibular joint function and dysfunction : a contemporary review = Explorando las complejidades de la función y disfunción de la articulación temporomandibular : revisión de literatura - Vinayak, Varun; Ram, K. Anisha; Chandran, Jithesh (2024)
This contemporary review delves into the intricate realm of temporomandibular joint (TMJ) function and dysfunction, shedding light on its multifaceted nature and offering insights into diagnostic and therapeutic strategies. The TMJ, a vital component of the craniofacial complex, plays a pivotal role in everyday activities such as chewing, speaking, and yawning. Understanding its anatomy and physiology is paramount in the treatment and management of TMJ dysfunction. The biomechanics of TMJ function, from the articular disc to the surrounding ligaments and muscles, have been explored comprehensively. A critical aspect of this review revolves around the diverse etiological factors contributing to TMJ dysfunction. Genetic predispositions, parafunctions, occlusal irregularities, and psychological stress are dissected to illuminate the roles of these factors in the development of TMJ disorders. These complexities prompted the need for a robust classification system elucidating the clinical manifestations and diagnostic criteria for various TMJ disorders. Modern diagnostic modalities, including clinical assessment, imaging techniques, and joint aspiration, are scrutinized for their indispensable roles in accurate diagnosis. The comprehensive overview included management strategies, from conservative measures to surgical interventions. In recognizing the pivotal influence of psychosocial factors, this review underscores the importance of patient-centered care and cognitive-behavioral interventions. Furthermore, regenerative therapies, minimally invasive techniques, and personalized medicine are emerging trends in TMJ research. This review provides a contemporary roadmap for comprehending, diagnosing, and managing TMJ-related conditions.
Esta revisión profundiza en el ámbito de la función y disfunción de la articulación temporomandibular (ATM), arrojando una luz sobre su naturaleza multifacética y ofreciendo información sobre estrategias diagnósticas y terapéuticas. La ATM, un componente vital del complejo craneofacial, desempeña un papel fundamental en actividades cotidianas como masticar, hablar y bostezar. Comprender su anatomía y fisiología es fundamental en el tratamiento y manejo de la disfunción de la ATM. Se ha explorado exhaustivamente la biomecánica de la función de la ATM, desde el disco articular hasta los ligamentos y músculos circundantes. Un aspecto crítico de esta revisión gira en torno a los diversos factores etiológicos que contribuyen a la disfunción de la ATM. Se analizan predisposiciones genéticas, parafunciones, irregularidades oclusales y estrés psicológico. Estas complejidades generaron la necesidad de un sistema de clasificación sólido que dilucidara las manifestaciones clínicas y los criterios de diagnóstico para diversos trastornos de la ATM. Las modalidades de diagnóstico modernas, incluída la evaluación clínica, las técnicas de imagen y la aspiración articular, son examinadas por su papel indispensable en el diagnóstico preciso. La descripción general integral incluyó estrategias de manejo, desde medidas conservadoras hasta intervenciones quirúrgicas. Al reconocer la influencia fundamental de los factores psicosociales, esta revisión subraya la importancia de la atención centrada en el paciente y las intervenciones cognitivo-conductuales. Además, las terapias regenerativas, las técnicas mínimamente invasivas y la medicina personalizada son tendencias emergentes en la investigación de la ATM. Esta revisión proporciona una hoja de ruta contemporánea para comprender, diagnosticar y tratar las afecciones relacionadas con la ATM.
En revista Odóvtos, vol. 26, no.3 (setiembre-diciembre 2024)
Descripción basada en el contenido visto el 07 de febrero, 2025
También disponible en formato HTML y EPUB